ANALISIS KINERJA KEUANGAN DAN ABNORMAL RETURN SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN SEKTOR NON-KEUANGAN DI BURSA EFEK INDONESIA - Aliffiyah Nur Fatimah (2022)
This study examines financial performance and abnormal returns with the intent of determining differences in financial performance and abnormal returns prior to and following a stock split. This study measured financial performance using three financial ratios: liquidity (CR), profitability (ROE), and market ratio (PER), with a two-year observation period preceding and following the stock split. This study's sample was selected using a criterion-based technique of purposive sampling, yielding 35 samples of companies listed on the Indonesia Stock Exchange that conducted stock splits between 2017 and 2019. The secondary data utilized in this study were evaluated using the Friedman test method in SPSS version 26. According to the findings of this study, liquidity and market ratio variables do not differ before and after a stock split. While there were differences in profitability and abnormal returns before and after the stock split, these differences were not significant.